Pengaruh Kepuasan Kerja Dan Komitmen Organisasi Terhadap Turnover Intention Pada Pegawai Honorer Dinas Perumahan Dan Kawasan Permukiman Kota Serang - Ayu Dila Adelia; Indri Indirasari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of job satisfaction and organizational commitment on turnover intention among temporary employees of Dinas Perumahan dan Kawasan Permukiman Kota Serang. This study uses an associative quantitative method with a statistical approach. Data was collected by distributing questionnaires to selected respondents. Data analysis was performed using multiple linear regression analysis. The regression analysis results show that job satisfaction has a significant effect on turnover intention with the regression equation Y = 7.723 + 0.154X₁ + 0.673X₂, regression coefficient 0.154 with Sig. 0.001 < 0.05, meaning that the higher the job satisfaction, the higher the turnover intention. Organizational commitment has a significant effect on turnover intention with the regression equation Y = 7.723 + 0.154X₁ + 0.673X₂, regression coefficient 0.673 with Sig. of 0.000 < 0.05, which means that if organizational commitment increases, turnover intention will increase. The simultaneous test results show that job satisfaction and organizational commitment together have a significant effect on employee turnover intention (Sig. 0.000 < 0.05). This proves that job satisfaction and organizational commitment together contribute to employee turnover intention.